2012
DOI: 10.1080/15459624.2012.635128
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characteristics and Spillage Mechanisms of Wall-Mounted and Jet-Isolated Range Hoods Subject to Influence from Cross Draft

Abstract: The effects of draft on the flow and spillage characteristics of wall-mounted and jet-isolated range hoods were investigated. A specially designed draft generator that could supply low-swirl air current was used to provide "cross draft" from three directions, lateral (θ = 0(o)), oblique (θ = 45(o)), and front (θ = 90(o)), with respect to the center point of the range hoods. Flow characteristics of oil mist were inspected through visualization of smoke flows with light scattering (laser light sheet-assisted vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To compare the results represented by Chen et al . 19 ) , the performances of the conventional and jet-isolated range hoods were obviously decreased when the draft velocity was higher than 0.3 m/s. The same result shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To compare the results represented by Chen et al . 19 ) , the performances of the conventional and jet-isolated range hoods were obviously decreased when the draft velocity was higher than 0.3 m/s. The same result shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…It was different from the effect of walk-by mentioned by Huang et al 18 , 21 ) . Chen et al 19 ) presented the containment of conventional range hoods operating under the effect of a cross draft. When the velocity of the cross draft was greater than 0.2 m/s, the pollutant spillage was increased with the increasing draft velocity.…”
Section: Introductionmentioning
confidence: 99%
“…When the rising thermal plume was disturbed by the makeup air, it would affect the capture area of the hood. Chen et al examined the hood performance under the effects of the cross draft from lateral, oblique, and front directions [34]. They found that cross draft could lead to the spillage of cooking emissions, and the effect worsened as the airflow velocity increased.…”
Section: Distribution Of Co 2 Concentration and Ce By Windowmentioning
confidence: 99%
“…Local exhaust ventilation (range hood) is an effective method to capture contaminants in residential buildings. To improve the efficiency for capturing contaminants and provide healthier indoor air quality, some innovative technologies had been studied: Aaberg hood [6][7][8][9][10][11][12], separation plate technology [13][14][15], air curtain technology [16][17][18][19][20][21][22][23], tornado-like suction airflow technology [24,25], and make-up air technology [26][27][28][29]. Some optimizations of the range hood have been proposed: Shaping the outlet [30], changing the structure of the fan [31,32], and adjusting some influential factors (airflow rate, dimension, and burner * Corresponding author: fl@byg.dtu.dk position of the range hood) [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%